LEED™ Platinum Awarded Arabian Green Building with Solar Heat Driven Cooling Technology. (June 2016) - Selke, Tim; Schubert, Moritz
Abstract: A gigantic sustainable tourism project is taking shape in the city of Al Ain by order of the government in Abu Dhabi. The Sheikh Zayed Desert Learning Center SZDLC is the first constructed building of the masterplan and functions as museum and research centre for desert environments and ecological issues. The building-owner set ambitious targets for sustainability and energy efficiency and the SZDLC has been already certified in the US program LEED™ (Leadership in Energy and Environmental Design) with the LEED™ Platinum Standard. With this paper two parts of the pioneering state-of-the-art architecture and technology of the SZDLC project are presented. Firstly a report on basic results of advanced energy modelling and simulation in the planning phase and for the certification method is given and secondly the authors publish energy performance data of the operating solar heat driven absorption cooling system.